Afektywne zdziwienia. Światem, ludźmi i literaturą. Interpretacja "Prolegomenów do wszelkich nauk hermetycznych" Michała Choromańskiego - Natkaniec, Daniel (Zagadnienia Rodzajów Literackich, 2024)
In this article, I introduce into the circulation of literary studies a deeper reflection on the affect of amazement. In my opinion, this category has aroused greater interest among philosophers than literary scholars over the centuries, which in a way entitles me to broadly discuss this omitted topic. Descriptions of this impulse, of course, often appear in scientific dissertations devoted to novels, drama or poetry, but most of them rarely go beyond the scheme of laconic, casual generalizations. To put it simply, they appear in passing, somewhere on the margin of other, more extensive investigations. This is a major oversight on the part of the savants. Therefore, this text, so to speak, fills a great gap in literary studies. I begin my considerations with a short theoretical introduction, in which I try to show how philosophers and writers have defined amazement in the past. Then, on the basis of the comments quoted, I formulate my own definition of this affect. In the latter part of the article, I turn theory into practice and use the term I proposed to interpret a specific novel — Prolegomena do wszelkich nauk hermetycznych (1958) by Michał Choromański, which is the first post-war work created by this author. In my analysis, I refer primarily to affective discourse to answer an important question: how did Choromański understand the mentioned concept? I believe that in Prolegomena do wszelkich nauk hermetycznych the writer presents his philosophy of amazement.